Hartree-Fock Calculations in Light Nuclei with Density Dependent Interactions - Lassey, Richard Keith (My University, 1972)
Hartree-Fock calculations have been performed using several density dependent two-body effective interactions in structural calculations of light even-even, N = Z nuclei. Two distinct types of interactions have been employed. The first are simple density and momentum dependent delta function interactions, of which several variants are derived to reproduce observed features in nuclear matter and in the nuclear surface and two of the:.;e are used in structural calculations. The second type of interaction has finite range and has been derived elsewhere to fit certain observed criteria. Two representatives of this type are utilized.
The calculations emphasize the important role played by the spin dependence of the interaction (the spinorbit interaction), and the resemblance of the density distributions that result from the calculation to clusters of alpha particles.
Keywords: Biology; Biology